Ethiopia Gender Diagnostic Report : Priorities for Promoting Equity - World Bank (World Bank, Washington, DC, 2019)
Ethiopia has experienced remarkable economic success in recent years. In the past decade, its average annual growth rate far exceeded the regional average, at slightly over 10 percent relative to a regional 5 percent. Despite significant economic growth, however, women continue to face significant barriers in the workforce. The unmet potential of women in the workforce is intrinsically linked to a lack of opportunities for women in education, health, and human rights. This report presents evidence on the mechanisms underlying gender gaps in the Ethiopian workforce. Using data from the 2011-2016 Ethiopia socioeconomic surveys, this report provides a detailed understanding of the constraints faced by female farmers, entrepreneurs, and employees. To that end, the diagnostic makes four key contributions: first, this report provides an overview of the labor force in Ethiopia and identifies the factors that predict whether, how much, and in what sector an individual works. Second, this report uses Oaxaca-blinder decompositions to measure and account for gender gaps in economic outcomes in agriculture, self-employment, and wage labor. Third, this report identifies the links between labor market skills, social norms, and gender gaps in the Ethiopian workforce. Fourth it provides policy makers with a menu of innovative programming examples.